Transformasi Komunikasi Interpersonal di Era IoT: Studi Budaya Digital di Masyarakat Indonesia - Sholikhaq, Amelia; Nugraha, Ayi Krisnha Widya Adhi; Adham, Ibnu (Jurnalika : Jurnal Ilmu Komunikasi, 2025)
This study explores the impact of interpersonal communication transformation influenced by the Internet of Things (IoT) on the quality of social relationships and the dynamics of digital culture within Indonesian society. Employing a qualitative approach with a case study design, this research examines individuals' experiences and perceptions of shifting communication patterns due to the integration of IoT devices in a culturally collective context. Data were collected through participant observation and digital documentation of interactions on social media platforms and messaging applications. The findings reveal that although IoT enhances connectivity and communication efficiency, excessive reliance on smart devices significantly reduces emotional depth and the quality of face-to-face interactions. Additionally, the study identifies selective adaptation in digital communication patterns, where Indonesian society leverages IoT to strengthen social networks without fully replacing warm and personal face-to-face interactions. These findings indicate a shift in interpersonal communication values, prioritizing efficiency and accessibility over emotional warmth. This study contributes to the development of digital communication theory within a collectivist cultural context and offers practical insights for technology developers and policymakers in designing adaptive and human-centered digital ecosystems. Future research should consider a longitudinal approach to explore the long-term effects of IoT usage on social interaction patterns and cultural value changes in digital society